Mechanical properties of sawdust concrete incorporating palm oil fuel ash - Nazar, Muhammad Salman (2013)
Malaysia being a very large producer of agro-waste, the high costs of building construction, environmental and sustainability issues have led to investigations into the use of agro waste as concrete products. Among others, sawdust and palm oil fuel ash (POFA) are complimentary materials when used in concrete. This project studies the use of sawdust, as fine aggregate replacement material in concrete also incorporating POFA. Sawdust is a lightweight aggregate, and can be used to wholly replace sand. POFA being a pozzolanic supplementary material imparts higher ultimate strength, improved workability and reduced watercement ratio. Sawdust concrete incorporating POFA has been investigated for its workability, strength, modulus of elasticity and above all for its suitability as a cheaper light weight concrete element. As expected, the 1:1 mix shows the higher strength’s and better durability while the 1:3 mixes have workability problems and lower strength’s but are cheaper in terms of cement use, not to mention the high (34.88%) utilization of waste materials. It is recommended that further study with a 0.5 water- cement ratio to the un-replaced cement only and a 1:2.5 mix ratio will reduce the gap between sawdust concrete incorporating POFA and normal concrete, hence making it a viable alternative.